Thermal performance evaluation of using aluminium oxide water-based nano fluids as coolant in hybrid collector - M.Elangovan, B.Srimanickam (International Journal of Modern Agriculture, 2021)
This research article deals with the thermal performance evaluation of using aluminium oxide water based nano fluids as a coolant in hybrid collector. There are two kinds of system can be designed and fabricated in this study. First one is standalone pv system which was performed electricity generation alone. This system can act as a reference of hybrid collector. Second one is water cum aluminium oxide nano fluid which can be generated both electricity and hot water production. Two types of volume flow rate were carried out in this article. Further, aluminium oxide with 0.05 % concentration acted along with water as a base fluid.The study results, which were analyzed from electrical and thermal viewpoints, have shown and revealed that the aluminium oxide-water nanofluid presented a better performance in terms of photovoltaic energetic conversion compared to standalone pv system. While aluminium oxide-water nanofluid revealed the highest thermal energetic efficiency. Moreover adding thermal unit to photovoltaic module (PV) enhanced the total energetic efficiency by 48.3 % for water, 57.2% for aluminium oxide-water.